Evaluación de dos productos acaricidas, jabón de coco y adjuvant (trisiloxano 100%) a tres dosis para el control de ácaros (tetranychus urticae) en el cultivo de frutilla (fragaria vesca l.) en el barrio el paraiso parroquia Huachi grande, cantón Ambato, provincia Tungurahua 2016 - Carrera Llano, Luis Eduardo (2016)
The present research project titled "Evaluation of two acaricidal products, Coconut Soap and Adjuvant (Trisiloxane 100%) at three doses for the control of Acaro (Tetranychus urticae) in the cultivation of Frutilla (Fragaria vesca) in the El Paraiso Parish Huachi Grande Canton Ambato Province of Tungurahua 2016. "; Whose general objective was; To evaluate two acaricidal products, Coconut Soap and Adjuvant (Trisiloxane 100%) at three doses for the control of Acaro (Tetranychus urticae) in the cultivation of Frutilla (Fragaria vesca). The method used was the experimental scientist of Block Completos al Azar (DBCA), as well as the hypothetical, deductive and the techniques used was field observation with data collection that was fulfilled every 2 days.